Interactions of the neural cell adhesion molecule and the myelin- associated glycoprotein with collagen type I: involvement in fibrillogenesis (The Rockefeller University Press, 1992)
To gain insights into the functional role of the molecular association between neural adhesion molecules and extracellular matrix constituents, soluble forms of the myelin-associated glycoprotein (MAG) and the neural cell adhesion molecule (N-CAM), representing most of the extracellular domains of the molecules, were investigated in their ability to modify fibrillogenesis of collagen type I. MAG and N-CAM retarded the rate of fibril formation, as measured by changes in turbidity, and increased the diameter of the fibrils formed, but did not change the banding pattern when compared to collagen type I in the absence of adhesion molecules. Scatchard plot analysis of the binding of MAG and N-CAM to the fibril-forming collagen types I, II, III, and V suggest one binding site for N-CAM and two binding sites for MAG. Binding of MAG, but not of N-CAM, to collagen type I was decreased during fibril formation, probably due to a reduced accessibility of one binding site for MAG during fibrillogenesis. These results indicate that the neural adhesion molecules can influence the configuration of extracellular matrix constituents, thus, implicating them in the modulation of cell-substrate interactions.